The Effect of Environmental Sanitation on the Risk of Acute Diarrhea in Children in Indonesia - Aisiyah, Adella; Hilmi, Indah Laily; Salman, Salman (Jurnal EduHealth, 2022)
Diarrhea is the second leading cause of death in children in Indonesia and 100,000 children under five die from diarrhea every year. The incidence of diarrhea in Indonesia reaches 6 million cases/year with every 756 cases there are 36 deaths. According to WHO (World Health Organization) it is estimated that there are 4 billion cases that occur worldwide with a total of 2.2 million deaths, most of which are children under 5 years of age. Acute diarrhea is caused by several factors, one of which is environmental factors such as lack of awareness of hygiene and sanitation. The method used in this study is a literature review by looking for articles related to the relationship between environmental sanitation and the incidence of diarrhea in children in Indonesia. The results showed that there was a relationship between environmental sanitation and the incidence of acute diarrhea in Indonesia.